THE LIFE AND WORK OF OGAHI (British Journal of Global Ecology and Sustainable Development, 2024)
This article is about the life and work of Muhammad Reza Ogahi, ideas of patriotism, creative activity, high appreciation of the pursuit of science, and according to Ogahi, the harmony between man and nature, the beauty of nature is a great factor in the development of the spiritual world of human thinking information about its importance is given.